Extrafollicular Cystic Adenomatoid Odontogenic Tumor of the Maxilla: a Rare Challenging Case Report with Review of the Literature - Soudabeh Sargolzaei; Saede Atarbashi-Moghadam; Farzad Aghdashi; Sara Mansouri Nejad (Mashhad University of Medical Sciences, 2018)
Adenomatoid odontogenic tumor is a non-aggressive slow growing epithelial odontogenic tumor with varied clinical and microscopic features. This neoplasm rarely appears as a completely cystic lesion histopathologically; therefore, oral pathologists should be aware of the various histopathologic types of this lesion. The main objective of this case report is to present a rare challenging case of maxillary extrafollicular cystic adenomatoid odontogenic tumor affecting a 28-year-old male.